Contracts with social multipliers - Mary A. Burke; Kislaya Prasad (Federal Reserve Bank of Boston, 2005)
We develop a model of contracting in which individual effort choices are subject to social pressure to conform to the average effort level of others in the same risk-sharing group. As in related models of social interactions, a change in exogenous variables or contract terms generates a social multiplier. In this environment, small differences in fundamentals such as skill or effort cost can lead to large differences in group productivity. We characterize the optimal contract for this environment and describe the properties of equilibria, properties that agree with stylized facts on effort compression in revenue-sharing settings. The model also implies potential sorting into groups on the basis of idiosyncratic effort costs. We estimate a significant social multiplier on physician productivity, using data on medical partnerships.
Keywords: 330; agency theory; peer pressure; social interactions; contracts; social multipliers